Hubungan Kualitas Layanan Kader Dengan Partisipasi Orang Tua Dalam Kegiatan Posyandu Di Kenagarian Jinang Kampung Pansur Kabupaten Pesisir Selatan - Sari, Lara Mailina; Ismaniar, Ismaniar (Universitas Negeri Padang, 2025)
This research is behind the low participation rate of parents in Posyandu activities in Kenagarian Jinang, Kampung Pansur, Pesisir Selatan Regency. This is suspected because the quality of cadre services in Posyandu activities has not been sufficient. This research aims to describe the quality of cadre services, parents' participation, and the relationship between cadre service quality and parents' participation in posyandu activities in Kenagarian Jinang Kampung Pansur, Pesisir Selatan Regency. This study used a quantitative approach with a correlational approach. The population in this study was 40 mothers, and a sample of 34 mothers. Samples are taken using random sampling. Data collection techniques using questionnaires. Data analysis techniques use the percentage formula and product moment. The results of this study show that: (1) cadre service quality is in the low category, (2) parents participation is also in the low category, and (3) there is a significant relationship between cadre service quality and parents participation in posyandu activities in Kenagarian Jinang, Kampung Pansur, Pesisir Selatan Regency. It is recommended that (1) Kader is expected to improve the quality of Posyandu services, (2) Parents are expected to participate more actively in all Posyandu activities, (3) Further researchers are expected to expand their research by exploring other variables.